Eco-functionality of organic matter in soils - Hoffland, Ellis; Kuyper, Thomas W.; Comans, Rob N. J.; Creamer, Rachel E. (Plant and soil, 2020)
Background Soil organic matter (SOM) supports multiple soil ecosystem functions, underpinned by processes such as C sequestration, N mineralization, aggregation, promotion of plant health and compound retention. We know little about the relationship between these functions and SOM quality. Scope We aimed to develop “eco-functionality” as a framework to address questions on the relation between SOM properties and soil ecosystem functions. Conclusions Paradigm shifts in SOM research have not led to metrics for eco-functionality beyond decomposability and C:N ratio. Recalcitrant OM is under-researched despite its essential role in aggregation and C sequestration, especially in C-saturated soils. Most soil functions are dependent on SOM decomposition and require labile compounds. We conclude that eco-functionality is context-dependent and needs to take time scales into account. We plea for attempts to link operationally defined SOM fractions to functions in order to make SOM research more applicable.